2019
DOI: 10.1124/dmd.118.085803
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Intestinal Monocarboxylate Transporter 6 Function and Expression in Diabetic Rats Induced by Combination of High-Fat Diet and Low Dose of Streptozocin: Involvement of Butyrate–Peroxisome Proliferator-Activated Receptor-γ Activation

Abstract: Generally, diabetes remarkably alters the expression and function of intestinal drug transporters. Nateglinide and bumetanide are substrates of monocarboxylate transporter 6 (MCT6). We investigated whether diabetes down-regulated the function and expression of intestinal MCT6 and the possible mechanism in diabetic rats induced by a combination of high-fat diet and low-dose streptozocin. Our results indicated that diabetes significantly decreased the oral plasma exposure of nateglinide. The plasma peak concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 73 publications
1
18
0
Order By: Relevance
“…All these results demonstrate that alterations in the expressions of hepatic CYP450s were involved in various mechanisms. In contrast to CYP2C6 induction, diabetes significantly lowered the expression of CYP2C11 [26,[47][48][49][50], impairing the metabolism of diclofenac [49], glibenclamide [48] and nateglinide [47]. The increase in CYP2C6 expression and decrease in CYP2C11 expression may partly explain why the AUC values of both phenytoin and 4 -hydroxylphenytoin in diabetic rats were comparable to control rats [51].…”
Section: Cyp450smentioning
confidence: 97%
See 2 more Smart Citations
“…All these results demonstrate that alterations in the expressions of hepatic CYP450s were involved in various mechanisms. In contrast to CYP2C6 induction, diabetes significantly lowered the expression of CYP2C11 [26,[47][48][49][50], impairing the metabolism of diclofenac [49], glibenclamide [48] and nateglinide [47]. The increase in CYP2C6 expression and decrease in CYP2C11 expression may partly explain why the AUC values of both phenytoin and 4 -hydroxylphenytoin in diabetic rats were comparable to control rats [51].…”
Section: Cyp450smentioning
confidence: 97%
“…In Caco-2 cells, it was reported that short-term exposure to sodium nitroprusside impaired P-gp function and expression, whereas long-term exposure stimulated P-gp function and expression [92]. Increased levels of short chain fatty acids (SCFAs) were also found in the intestinal content of diabetic rats [47]. A recent study showed that SCFAs downregulated the expression of intestinal P-gp via inhibiting histone deacetylase and NF-κB pathways [93].…”
Section: P-gpmentioning
confidence: 99%
See 1 more Smart Citation
“…While there were significant changes between the wild-type and Mct6 −/− mice associated with lipid metabolism, there were no significant differences reported in major enzymes involved in PG elimination or synthesis, such as dehydrogenase and synthase/reductase enzymes. Additionally, Xu et al suggested the involvement of butyrate-mediated Pparγ activation on Mct6 regulation in diabetic rats [12]. This suggests that Mct6 is regulated, in part, via PPAR-dependent mechanisms, which play a role in regulation of lipid metabolism, and effectively, PG homeostasis.…”
Section: Diet-dependent Evaluation Of Pgf2α and Pgfm Concentrations Imentioning
confidence: 99%
“…From this study, Zhang et al found that Slc16a5 was upregulated~5-fold following a fasted diet compared to a normal diet, making it one of the top 15 fold-change genes upregulated by fasting out of the 2305 genes found to be significantly regulated by food availability. More recently, Xu et al showed that MCT6 may play a role in dietary metabolic pathways using a rat model of diabetes [12]. While the amino acid sequence identity between murine Mct6 (mMct6) and human MCT6 (hMCT6) is relatively similar (~68% according to Clustal Omega), very little data exists regarding the correlation between mMct6 and hMCT6 activity.…”
Section: Introductionmentioning
confidence: 99%